PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PEMBUANGAN BAYI YANG BARU DILAHIRKAN - Syarifah Nurhalizah; Sabina Salsabila (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Child is someone who is not yet 18 (eighteen) years old, including children who are still in the womb. Children are the nation's next generation who need special legal protection that is different from adults, due to the physical and mental conditions of children who are immature and mature. However, it cannot be denied that there are still many cases of child abandonment, especially for newborns. The research method used is a secondary data source that collects data obtained from previously created documents. In the context of this research, the analysis carried out relates to law enforcement against the elements of the crime of disposal of newborn children, and law enforcement against perpetrators of disposal of newborn children, as well as discussing the accountability of perpetrators of disposal of newborn children in achieving goals. study. The perpetrator of the crime of disposing of a newborn child is the mother herself because she is afraid that the community will find out that she has given birth to a child. The fear of being found out is usually caused because the child is the result of an illicit relationship or outside of marriage. An action that is a rule of law declared as an act that is prohibited is called a criminal act or can be referred to as a crime. There are 3 (three) legal instruments that contain criminal sanctions against perpetrators of the crime of disposal of babies/children, namely the Criminal Code, Law no. 23 of 2004 concerning the Elimination of Domestic Violence, and Law Number 35 of 2014 concerning Child Protection. However, the perpetrators of violence against newborn children have not been eliminated, and one of the factors is the lack of confidence in criminal charges.